Fiscal Monitor, April 2014 : Public Expenditure Reform: Making Difficult Choices. (Washington, D.C. : International Monetary Fund, 2014)
Fiscal risks are abating somewhat but remain elevated. In advanced economies, recent policy moves have broadly stabilized public debt ratios, but medium-term prospects are still uncertain, and debt remains at historic highs. Fiscal vulnerabilities are rising in both emerging market economies and low-income countries, although in most cases from relatively moderate levels. Across country groups, fiscal policy should aim at rebuilding policy space while supporting the recovery and long-term growth prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet